The trend of sharenting among Malaysian parents: a qualitative study on their content and motivation - Lee Jia Wen; Crendy Tan; Saroja Dhanapal (Intelektual Pustaka Media Utama, 2022)
With social media having penetrated people’s daily life, sharenting has become a common phenomenon among the current generation. The term “sharenting” is derived from the combination of the words “share” and